Judging A Book By Its Cover Exploring Body Modification and Employment - Doherty, Sarah Rose (2014)
This work aims to understand the relationship between body modifications and employment. The body has received much academic attention recently, yet the experience of modified bodies’ remains overlooked, particularly within the workplace. This is surprising considering the centrality of the individual within the UK’s growing service industry. In using the legal industry as its focus, this study reveals the taken-for-granted assumptions regarding ability and the body which are present throughout the contemporary job market. Data was collected through a series of interviews with individuals with body modifications and with individuals working at a large Midlands-based legal firm. In contributing to current understandings of the organisational management and the sociology of the body, this work makes evident the importance of the body within the workplace and discusses the shift in meaning of body modifications in society. In so doing, this work reveals the disparity in treatment between certain bodies and the way in which ‘choice’ is used to legitimate workplace discrimination. Its findings have implications for future bodily research and current understandings of hiring and promoting practice within the job market.